Evaluation Of Toxicity, Pharmacokinetic And Clastogenicity Profile Of Ethyl 2-[4[(Piperidin-1-yl) Phenyl]-1h-benzimidazole-5-carboxylate (Bzd9l1), Novel Sirtuin Inhibitor - Lee, Yeuan Ting (2022)
The mammalian sirtuins (SIRTs) have been linked to various diseases including cancer, diabetes, neurodegenerative and cardiovascular diseases. Thus, SIRTs are attractive targets for the development of pharmaceuticals. The lack of potential SIRT inhibitors in cancer clinical trials highlights the need to develop a potent SIRT modulator as an anti-cancer therapeutic. Studies in the lab have highlighted the capability of a lead sirtuin inhibitor (BZD9L1) to reduce colorectal tumour growth in vitro and in vivo by modulating different cancer pathways in colorectal cancer with different mutation profiles. Also, synergistic effects of BZD9L1 in in vitro assays and tumour xenograft study when used in adjunct with 5- Fluorouracil (5-FU) further support the promising therapeutic effects of BZD9L1 as anticancer regime. Nevertheless, the toxicology profile of this compound remains unknown. To our knowledge, no prior work has reported the regulation of SIRTs in the liver and kidney by a small molecule inhibitor in a drug toxicity study. Therefore, this project aims to determine the toxicology, molecular regulation of toxicity, pharmacokinetics and clastogenicity profiles of BZD9L1 in in vitro or in vivo models